2013
DOI: 10.1063/1.4807092
|View full text |Cite
|
Sign up to set email alerts
|

Size effects on water adsorbed on hydrophobic probes at the nanometric scale

Abstract: Molecular dynamics simulations of liquid water at ambient conditions, adsorbed at the external walls of (n,n) single-walled armchair carbon nanotubes have been performed for n = 5, 9, 12. The comparison with the case of water adsorbed on graphene has also been included. The analysis of Helmholtz free energies reveals qualitatively different ranges of thermodynamical stability, eventually starting at a given threshold surface density. We observed that, in the framework of the force field considered here, water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Since previously reported MD simulations have shown that water molecules form a layer-like structure when interacting with the surface of a CNT, [20][21][22][23][24] the physisorbed water molecules are modeled as a layer which adheres to the previously reported density profile (see Figure 1b). [21] As illustrated by Figure 1d, the wall defects of the CNTs allow for unrestricted adsorption of Kr molecules, but since water molecules require large openings ( 0.6 nm due to an equilibrium water-CNT wall separation of ∼ 0.3 nm [21]) to access the internal region of the CNT, the adsorption of the water molecules is taken as only exohedral in nature (see Figure 2b for an illustration of the model geometry).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previously reported MD simulations have shown that water molecules form a layer-like structure when interacting with the surface of a CNT, [20][21][22][23][24] the physisorbed water molecules are modeled as a layer which adheres to the previously reported density profile (see Figure 1b). [21] As illustrated by Figure 1d, the wall defects of the CNTs allow for unrestricted adsorption of Kr molecules, but since water molecules require large openings ( 0.6 nm due to an equilibrium water-CNT wall separation of ∼ 0.3 nm [21]) to access the internal region of the CNT, the adsorption of the water molecules is taken as only exohedral in nature (see Figure 2b for an illustration of the model geometry).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies on how water interacts with the outer surface of a CNT illustrated that the water molecules form a layer-like shell surrounding the CNTs, [20][21][22][23] and that the water layer density varies greatly and non- * wardle@mit.edu.…”
mentioning
confidence: 99%
“…Once the b ij coefficients are known, Calero et al [52] compute F(ρ, T) in Equation (1), as reported in Figure 2 for T = 298 K. Curves for T = 310 and 323 K (not shown) are similar to those for 298 K, but displaced to lower values of F. From the the minima and the shape of F as function of ρ and T one can evaluate the stability of the adsorbed water layer.…”
Section: Thermodynamic Stabilitymentioning
confidence: 99%
“…Calero et al [52] calculate the radial oxygen density profiles of water and the corresponding hydrogen-bond (HB) distributions. They adopt a geometrical definition of the HB in which two water molecules are H-bonded when their oxygen-oxygen distance is d OO < 3.37 Å and the OOH angle is < 30 • [54].…”
Section: Structure and Hydrogen Bondingmentioning
confidence: 99%
See 1 more Smart Citation